GF14f gene is negatively associated with yield and grain chalkiness under rice ratooning - Lin, Feifan; Lin, Sheng; Zhang, Zhixing; Lin, Wenxiong; Rensing, Christopher; Xie, Daoxin (Frontiers in Plant Science, 2023)
Ratoon rice cropping has been shown to provide new insights into overcoming the current challenges of rice production in southern China. However, the potential mechanisms impacting yield and grain quality under rice ratooning remain unclear. In this study, changes in yield performance and distinct improvements in grain quality in ratooning season rice were thoroughly investigated. Rice ratooning induced an extensive carbon reserve remobilization in combination with an impact on grain filling, starch biosynthesis, and ultimately, an optimization in starch composition and structure in the endosperm. Furthermore, these variations were shown to be associated with a protein-coding gene: GF14f (encoding GF14f isoform of 14-3-3 proteins) and such gene negatively impacts oxidative and environmental resistance in ratooning season rice. Finally, our findings also suggested that this genetic regulation by GF14f gene was the main cause leading to changes in rice yield and grain quality improvement of ratooning season rice, irrespective of seasonal or environmental effects. A further significance was to see how yield performance and grain quality of ratooning season rice were able to be achieved at higher levels via suppression of GF14f.